Gauging the Gap: Inequality of Time Use When Seeking Government Services - Andrea Briceno-Mosquera; Sharon Mastracci (Journal of Social Equity and Public Administration)
Seeking government services and interacting with the administrative state require time and waiting. However, the use of time while interacting with the administrative state is unevenly distributed across racialized groups. Using data from the American Time Use Survey (ATUS) 2003–2022, we examine inequities when seeking and waiting for government services. Blacks wait 1.7 times longer, and Hispanics wait 1.6 times longer than Whites when seeking government services. Individuals without a partner, with more household children, and the unemployed also devote more time waiting for government services. This article contributes to the scholarship on administrative burdens by arguing that uneven wait time distribution may result from racialized administrative procedures. Those who spend more time seeking government services and waiting experience higher opportunity costs that interfere with their lives, reproducing and normalizing injustices. Uneven wait times may also engender animosity toward the administrative state among already marginalized individuals.